O Cogito como primeiro princípio - Ibrahim, Samir (2007)
It examines, in the First, Second and Third Meditations the cogitate as first principle of the Cartesian philosophy. It accomplishes a detailed analysis of the constitution and of the role of the doubt as instrument on which the lack of solidity of the foundations is evidenced on which were settled the "old opinions" even Discards. In this analysis, is distinguishes the different levels of the doubt; the function that it carries out in each one of the different levels in the taskwork to demonstrate the doubt-ability that each class of opinions contains, and as aim the different principles on which each class is sustained; it demonstrates which way the doubt happens on the principles susceptible to suspicion. It verifies which the features that do the cogitate the first principle of this philosophy in opposition to the other such indubitable elements as the "common notions". It examines the way on which the spirit achieve to the conception of this indubitable certainty on which the first principle is established and I concluded that it is treated of the intuitive way. It compares and it distinguishes the different principles of this philosophy such as doubt, cogitate and God. It determines the conditions of possibility of any indubitable knowledge. It determines the possibility conditions for the science properly based. It comments on and presents a possible solution for the subject of the circle in the Cartesian system. It describes how occur the linkage process of the reasons leaving properly of the first principle to the conquest of the first scientific truth, in other words, God. It compares, it relates and it distinguishes the three certainty orders: mathematical certainty, certainty of the first principle, certainty of the existence of a veracious God. Finally, it differentiates the progress of the lineal knowledge and right ordered of the progress that settles down for the net of multiple connections between the reasons and the truths and it diagnoses the second as being the model for which the Cartesian system, in fact, settles down.